THE COVID-19 VACCINATION AS FULFILLMENT THE RIGHTS PRISONER TO GET HEALTH SERVICES - Abdullah Mulyadi Gani; Baharudin Baharudin; Lintje Anna Marpaung (Universitas Labuhanbatu, 2023)
The enforcement of the Circular Letter of the Director General of Corrections Number: PAS-20.PR.01.01 of 2020 concerning progressive steps in controlling the spread of Corona Virus Disease (Covid-19) at the Correctional Technical Implementing Unit is a policy taken in the context of implementing the Covid-19 vaccination at the Correctional Institution Class II Narcotics Bandar Lampung. The purpose of this research are to describe the implementation of the Covid-19 vaccination in the Class II Narcotics Prison in Bandar Lampung as a fulfillment of the rights of the inmates to obtain health servicesand the inhibiting factors for the implementation of the Covid-19 vaccination at the Class II Narcotics Prison in Bandar Lampung. The research using n0rmative and juridical appr0ach.Â The results 0f this study indicate that theÂ Covid-19 Vaccination at the Class II Narcotics Prison in Bandar Lampung as a fulfillment of the rights of the inmates to obtain health services has been carried out even though not maximal. The implementation of vaccination was 974 prisoner, consisting of 796 prisoner who had undergone the first vaccination, 795 prisoner had undergone the first and second vaccination, 172 prisoner had undergone the first, second and third vaccination. A total of 6 inmates have not been vaccinated because they suffer from comorbidities (2) The inhibiting factors for the implementation of the Covid-19 Vaccination at the Class II Narcotics Prison in Bandar Lampung consist of barriers to the identity of the inmates, namely the duplication of prisoner data, the presence of inmates who do not have ID cards and there is no access to communication to the family of the inmate to confirm the resident number of the inmate. In addition, there are prisoner who suffer from comorbidities so that vaccination cannot be carried out.Keywords: Covid-19 Vaccination, Correctional Inmates, Health